(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
A rod with a stepped non-uniform cross-section, rigidly fixed at both ends, is subjected to concentrated axial loads (Fig.1). It is required to construct the diagrams of axial forces, normal stresses, and axial displacements. In the calculations, assume